Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11033-013-2582-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic genetic variation in immune system genes: a study of two populations of Espirito Santo, Brazil

Abstract: Mapping single nucleotide polymorphisms (SNPs) in genes potentially involved in immune responses may help understand the pathophysiology of infectious diseases in specific geographical regions. In this context, we have aimed to analyze the frequency of immunogenetic markers, focusing on genes CD209 (SNP -336A/G), FCγRIIa (SNP -131H/R), TNF-α (SNP -308A/G) and VDR (SNP Taq I) in two populations of the Espirito Santo State (ES), Brazil: general and Pomeranian populations. Peripheral blood genomic DNA was extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
6
8
0
Order By: Relevance
“…Age, gender, reinfection, acute phase medication, race and viral characteristics may influence dengue outcome of [30]. In our study, we have found a longer persistence of symptoms in females patients, which is in agreement with García et al…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Age, gender, reinfection, acute phase medication, race and viral characteristics may influence dengue outcome of [30]. In our study, we have found a longer persistence of symptoms in females patients, which is in agreement with García et al…”
Section: Discussionsupporting
confidence: 92%
“…SNPs genotype distribution in symptomatic dengue patients remained similar to the normal ES population genotype distribution, as demonstrated in previous studies performed by us like Dettogni et al [30] and other work not yet published.…”
Section: Snps and Persistent Clinical Symptomssupporting
confidence: 88%
“…In addition, there was no statistically significant difference in allele and genotype distribution between the Pomeranian subpopulation and general population in our study. This result confirms other data that reported gene flow between the general and Pomeranian populations of ES (Stur et al, 2012;Dettogni et al, 2013).…”
supporting
confidence: 92%
“…In the study, the frequency of allele -336G was 29.7% in a naturally mixed population, a frequency that does not differ statistically from the frequency we observed (20.2% in a mixed population in northeastern Brazil). Although the frequency of CD209 SNP -336A/G found in this study was similar to the frequency found in other Brazilian regions (Xavier-Carvalho et al, 2013;Oliveira et al, 2014), it was significantly lower than that found in a population in the southeast, where the observed frequency was 37.5% (P < 0.05) (Dettogni et al, 2013). However, a higher frequency of allele -336G has been observed even in neighboring Piauí states such as Pernambuco; the allele frequency in the study performed by Silva et al (2012) was 31.4% (P = 0.052).…”
Section: Discussionsupporting
confidence: 66%